Analisis kesalahan struktur kalimat dasar pada keterampilan menulis teks wawancara peserta didik kelas iv sekolah dasar - Puspawati, Yunita Dwi; Slamet, Slamet; Surya, Anesa (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
This research aims to describe basic sentence structure errors and describe the factors that cause basic sentence structure errors in writing interview text skills. This research is a descriptive qualitative research. The research subjects were fourth grade students, fourth grade teachers, and the principal of SD Negeri Tegalsari. Data collection techniques used interviews, documentation studies, and observation. The data validity test technique uses source triangulation and technical triangulation. The data analysis technique uses an interactive analysis of the Miles and Huberman model which includes four stages: (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions. The results showed that the analysis of basic sentence structure errors on the subject indicator (19.23%), predicate indicator (13.46%), object indicator (8.65%), description indicator (45.2%), and complementary indicators (13.46%). Based on the results of the study, it can be concluded that the analysis of basic sentence structure errors in the description indicator is the indicator that most errors occur in the use of sentences. The theoretical implications can be used as a reference for further research. The practical implications can help educators understand how students understand basic sentence structures and to improve future learning.